(untitled) - Sinha, Radha (Tokyo, 1983)
Japan’s economic success since the 1950s created a range of serious domestic and international problems which threaten the stability of the country. Within Japan at the start of the 1980s there was a strong mood on the right for remilitarization to give the nation the super-power status her economic performance justified. Outside Japan, there was increasing pressure from the West to make her conform to Western strategic interests. Against the background of these crucial issues the book analyzes the economic, political and military options open to Japan. Focussing on the interconnecting themes of foreign harassment and domestic economic disorder, the author points out many areas of similarity between Japan of the 1930s and Japan of the 1980s.
Keywords: Japan,Japan,Nhật Bản,Nhật Bản; Foreign economic relations,Politics and government,Quan hệ kinh tế đối ngoại,Chính phủ và chính sách; 1945-,1945